The Modeling Classification of the Crown of Aristocrat Women of Song Dynasty - Zhang, Shuhua; Musdi, Shanat; Qistina Donna, Lee Abdullah
A crown is one of the numerous headgear decoration of ancient Chinese women, Chinese women reached the peak of wearing a crown in the Song Dynasty. Especially the crowns of aristocratic women in the Song Dynasty, with rich categories, exquisite luxury and matchless ingenuity.This paper uses three materials: written records in ancient books, legacy of historical images and archaeological objects unearthed to analyzes and classifies the crowns and ornaments of aristocrat women in the Song Dynasty. The crown of aristocrat women in the Song Dynasty can be divided into the ritual crown and informal crown, which can be further subdivided from the aspects of shape and material.Through the case study of the typical crown, the crown decoration style of the aristocratic women in the Song Dynasty can be restored and reproduced to the greatest extent. This paper also provides a better understanding of the lifestyle of women in the Song Dynasty.